2016
DOI: 10.5993/ajhb.40.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe and Cigarette Smoking among University Students in the Western Cape, South Africa

Abstract: Waterpipe smoking in the Western Cape is widespread, but less than cigarette smoking. Because all tobacco products are harmful, the government has an obligation to impose appropriate regulatory measures to reduce waterpipe consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 17 publications
5
22
1
Order By: Relevance
“…The age of the first consumption of waterpipe in the current research was 17.9 (±3.9) years, the age of starting to consume waterpipe was 18(±3.4) years in Tehran [14], 18(±2.5) years in Saudi Arabia [21], and 16(±2.81) years in South Africa [20], 19(±5.84) years in the United States [16], indicating lack of a significant difference between the domestic and foreign studies. Comparing the frequency of waterpipe consumption among males and females demonstrates higher consumption of it among males, and this result is seen in many domestic and foreign studies [11, 12, etc.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The age of the first consumption of waterpipe in the current research was 17.9 (±3.9) years, the age of starting to consume waterpipe was 18(±3.4) years in Tehran [14], 18(±2.5) years in Saudi Arabia [21], and 16(±2.81) years in South Africa [20], 19(±5.84) years in the United States [16], indicating lack of a significant difference between the domestic and foreign studies. Comparing the frequency of waterpipe consumption among males and females demonstrates higher consumption of it among males, and this result is seen in many domestic and foreign studies [11, 12, etc.…”
Section: Discussionmentioning
confidence: 76%
“…In the United States, Leavens et al [16], Heinz et al [17] and Noonan [18] reported the history of waterpipe consumption as 35.3%, 48% and 61%, respectively. It has been also reported 66% in England [19], 32.2% in South Africa [20], 37% in Saudi Arabia [21], 41.9% in Lebanon [22], and 56% in Jordan [23] students. In general, waterpipe consumption has increased in different communities and in different cultures, and it is mostly seen among adolescents and young people, thus high frequency of waterpipe consumption among students in different countries is predictable.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations